Determination of Bisphenol A by a Gold Nanoflower Enhanced Enzyme-Linked Immunosorbent Assay. (2nd July 2016) - Peng, Chifang; Pan, Na; Xie, Zhengjun; Liu, Liqiang; Xiang, Jie; Liu, Chunli
ABSTRACT: The use of nanomaterials to improve the sensitivity of enzyme-linked immunosorbent assays (ELISA) for small molecules allows wider application of this method. In this work, gold nanoflowers were synthesized by a seed-mediated procedure and used to prepare a horseradish peroxidase-immunoglobulin G-gold nanoflower complex. The complex was used as the signal amplification probe in a novel ELISA for bisphenol A. The gold nanoflower-enhanced ELISA demonstrated excellent detection sensitivity of 0.05 ng/mL, which was 20 times more sensitive than a standard ELISA procedure. A linear dynamic range from 0.1 to 5.0 ng/mL was obtained by this approach. The gold nanoflower-enhanced ELISA was used to determine bisphenol A in lake water, with recoveries from 92.0 to 102.0% in samples fortified at concentrations of 0.5, 1.0, and 3.0 ng/mL. The gold nanoflower-enhanced ELISA was shown to offer good sensitivity, simplicity, and low cost.